HELP-VDL: study protocol for a multicentre, open, randomised, controlled clinical trial comparing the use of the head-elevated laryngoscopy position and the use of a videolaryngoscope to facilitate orotracheal intubation in a patient population without predictable difficulty of intubation. Issue 7 (8th July 2020) - Le Guen, Morgan; Coppere, Zoé; Dufour, Guillaume; Ouattara, Jonathan; Trichereau, Julie; Fischler, Marc
Abstract : Introduction: Tracheal intubation remains an everyday challenge for anaesthesiologists, even in patients without suspected difficult airways. The ideal positioning of the patient's head (flat, raised a few centimetres on a cushion in the sniffing position (SP), or raised to achieve horizontal alignment between the external acoustic meatus and the sternal angle) and the use of videolaryngoscopy remain controversial. This trial aims to compare the efficacy for orotracheal intubation of the SP or the head-elevated laryngoscopy position (HELP), which has been shown to improve laryngeal visualization and the intubation condition particularly in obese patients, in combination with a McGrath Mac videolaryngoscope whose video screen is either on or off (Video or NoVideo). Methods and analysis: The HELP-VDL factorial trial is a prospective, randomised, parallel, multicentre, open study of 240 adult patients undergoing tracheal intubation under general anaesthesia. Patients will be allocated into four groups: SP-NoVideo, HELP-NoVideo, SP-Video and HELP-Video. The primary outcome is the proportion of orotracheal intubations that requires the assistance of a nurse anaesthetist. The secondary outcomes include the intubation duration, the first intubation success rate, the quality of visualisation of the glottis, the glottis visualisation score, adjunctive manoeuvres and alternative techniques used, the occurrence of oesophageal intubation, failure of tracheal intubation, the incidence of arterial oxygen desaturation, the perception of a difficult intubation, the score on the Intubation Difficulty Scale, cooperation among the members of the anaesthesia team, the evolution of vital signs and the frequency and severity of intubation complications. Data will be analysed on the intention-to-treat principle and a per-protocol basis. Ethics and dissemination: Ethics approval was obtained from the Ethical Committee Ile de France V (Paris, France). Participant recruitment began on 3 July 2019. The results will be submitted for publication in peer-reviewed journals. Trial registration number NCT03987009; Pre-results.